2007
DOI: 10.1080/13557850701300707
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Considerations in Developing Church-Based Programs to Reduce Cancer Health Disparities Among Samoans

Abstract: Our findings inform programming, and our consumer-oriented process serves as a model for others working with minority churches to reduce cancer health disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 20 publications
0
57
0
Order By: Relevance
“…Given the complexities of heart failure care, building the capacity of family caregivers to meet the informational and tangibleinstrumental support needs of a heart failure patient could reduce the psychological distress caused by the illness as well as improve its management among Pacific Islanders. Other studies among Native Hawaiians and Samoans have also highlighted the importance of educating and marshalling the support of family members in chronic disease management and the training of assertiveness skills for patients and family members to communicate more effectively with their healthcare providers (58,59).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the complexities of heart failure care, building the capacity of family caregivers to meet the informational and tangibleinstrumental support needs of a heart failure patient could reduce the psychological distress caused by the illness as well as improve its management among Pacific Islanders. Other studies among Native Hawaiians and Samoans have also highlighted the importance of educating and marshalling the support of family members in chronic disease management and the training of assertiveness skills for patients and family members to communicate more effectively with their healthcare providers (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…As several studies note, Samoans differentiate between palagi (Western illnesses) and ma'i Samoa (illnesses specific to Samoans) (58,69). The first category may be treated and cured through Western medicine; the second cannot and requires the intervention of a fofo or traditional healer (58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2734 CBPR methods also informed the development of health education materials and interventions that were attractive to and welcomed by the community. 18,25,30,35–38 Many CNPs successfully employed community members in intervention delivery.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 For migrant Samoans, churches supplant villages as primary locations for socialization 31 and have potential for use as a venue to promote disease risk reduction. Studies have partnered with Samoan churches to successfully recruit participants, promote nutrition interventions, [31][32][33][34] and encourage use of mammography. 33 Focus groups conducted among Samoan participants in Hawaii selected through keyinformant referrals from Samoan community members 35 demonstrated that the church was an appropriate setting to address obesity.…”
Section: How Can Evidence Be Translated To Evidence-based Practice?mentioning
confidence: 99%